AB0949 Treatment in mono-/oligo- and polyarthritic patients; a study on the swedish early psoriatic arthritis cohort (SWEPSA). (23rd January 2014) - Lindqvist, U.; Husmark, T.; Alenius, G.-M.; Larsson, P.T.; Teleman, A.; Geijer, M.; Theander, E.
Abstract : Background: The diverse features of psoriatic arthritis (PsA) with clinical classification changes over time and with difficulties to outline treatment recommendations causes suboptimal assessment in many cases. Objectives: Patients with symptoms and signs of PsA have been documented in the Early Swedish Psoriatic arthritis Register (SwePsA). Methods: Patients referred to the clinics within two years of onset of PsA were included in the register and followed up according to the program for SwePsA (1). Classification at inclusion and 5 years later was performed by the same rheumatologists according to the ClASsification Criteria for Psoriatic Arthritis (CASPAR) or ASAS. Results: At classification on inclusion patients with mono- or oligoarticular (MO) disease were most frequent with 47% of 208 patients. Forty-two percent were classified as polyarticular (P) disease. Nine percent had axial involvement and 2% were in remission. One third of patients with MO disease were treated with DMARD. At reclassification on 5 year followup 80% remained MO patients and 18% were in remission. Treatment of 55% of P patients with DMARD or anti-TNF-alpha was performed and at reclassification after 5 years 40% had a MO disease and 8% were in remission (p=0.041). Minimal disease activity (MDA) (2) was assessed and patients with MO disease had significantly more frequent MDA compared to P patients at 5 year followup (p=0, 047). Treatment of MO patients did not improve the number of patients reaching MDA at reevaluation. Neither was there any significant difference between treated and untreated MO patients reaching remission at 5 year followup. Also patients with P disease did not fulfill the criteria for MDA more often if treated with DMARD and/or anti-TNF-alpha compared to nontreated patients. On the contrary all P patients that reached remission were nontreated patients (p=0.006). There was a gender difference with more men reaching MDA (p=0.006) and remission (p=0.043) compared to women at 5 year followup. MDA and remission was achieved more frequent in patients before 40 years of age- Conclusions: The effects of treatment in PsA patients in clinical practice are not clear-cut and need to be further evaluated. References: Lindqvist U, Alenius G-M, Husmark T, Thunder E, Holmström G. For the Psoriatic Arthritis Group of the Swedish Society for Rheumatology. The Swedish early psoriatic arthritis register: two-year follow up. A comparison with early rheumatoid arthritis. J Rheumatol 2008;35:668-73 Coates L, Cook R, Lee KA, Chandran V, Gladman DD. Frequency, predictors, and prognosis of sustained minimal disease activity in an observational psoriatic arthritis cohort.Arthritis Care Res 2010;62:970-6 Disclosure of Interest: None Declared